PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI, MOTIVASI DAN, DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PT. BANK TABUNGAN NEGARA (PERSERO) TBK KANTOR CABANG SURAKARTA - Muhammad Maulana DA; Kasidin Kasidin (STIE Atma Bhakti, 2019)
The research purposes was determined the effect of leadership style, compensation, motivation, and work discipline on the productivity of the employees of PT. Bank Tabungan Negara (Persero) Tbk Surakarta Branch Office. This research was used descriptive method and the sample used 60 respondents with a sampling technique used the accidental sampling method. Data collection methods are questionnaires, observations, interviews and literature study. The research instrument was used the linkert scale method with 5 answer criteria. Hypothesis test results consisting of the results of the analysis of multiple linear regression equations shown the value of beta (β) of each variables of leadership style, compensation, motivation and work discipline shows a positive number. The results of the t test analysis showed that each variable has a value of tcount > t table and has a significance value